The Effect Of Capital Adequacy Ratio, Return On Asset And Financing To Deposit Ratio On Murabahah Financing Islamic Commercial Banks In Indonesia - Fery Rahma Pradika; Fatchur Rohman (Jurnal Rekognisi Akuntansi, 2022)
This study aims to determine the effect of Capital Adequacy Ratio, Return On Assets and Financing to Deposit Ratio on Murabahah Financing in Islamic Commercial Banks in Indonesia..The data used is secondary data, the time dimension of research data uses time series data. In this case the researcher obtained secondary data from the financial reports of Islamic commercial banks through the Financial Services Authority. The population in this study is all Islamic commercial banks registered with the Financial Services Authority (OJK) from 2016 - 2020. In this study the sample used was all data from the population. Methods of data analysis in quantitative research are Descriptive Statistics, Classical Assumption Test, Multiple Regression Analysis and Hypothesis Testing (Model Feasibility Test (F), Partial Test (t), Coefficient of Determination Test (R2)). The analytical tool used is multiple linear regression analysis with the SPSS 25 program and a significance level of 5%..The results of hypothesis testing show that there is evidence that the Financing to Deposit Ratio variable has a positive effect on murabahah financing, while the Capital Adequacy Ratio and Return On Assets variables have no effect on murabahah financing.